Correlation between mechanical and structural properties as a function of temperature within the TeO2–TiO2–ZnO ternary system - de Clermont-Gallerande, J.; Dutreilh-Colas, M.; Célarié, F.; Gueguen, Y.; Bergler, Michael; de Ligny, Dominique; Hayakawa, T.; Thomas, P. (Journal of Non-Crystalline Solids, 2019)
In situ Raman spectroscopy, Resonance Frequency and Damping Analysis (RFDA) setup and Associated Raman Brillouin Calorimeter (ARABICA) setup experiments as a function of temperature were conducted on the (100-x)TeO2–5TiO2–xZnO (x = =15; 17.5; 20; 22.5; 25) glass system. Structural and mechanical properties showed non-conventional properties evolution as a function of ZnO content which are managed by the modification of ZnO polyhedra. Before glass transition temperature (Tg), the evolution of the Boson peak (BP) frequencies and the elastic properties are in accordance with the idea of the relaxation of the strains inside the glass; after Tg, their evolution shows the transition toward a viscous liquid. BP and mechanical properties study evidences that as nano-heterogeneous domains size increases at a faster rate, the mechanical properties will decrease at a slower rate. This point will be helpful for choosing appropriate composition for optical fiber shaping.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Brillouin; Glass; Raman; RFDA; Tellurite